Diagnostic Evaluation for Mastery learning of Algebra Subject Matter in the Mathematics Curriculum for the 3rd. Intermediate Grade Students in Iraq - AL mayoof, R.B.A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Inspite of the renovation and development that occurred on themathematics curricula and its teaching styles (methods), the teaching methods and the evaluation styles that the teachers of the countryfollow  are  still  traditionaL It depends  on  the  normal distribution approach and the principle of individual differences among students inaddition the traditional tests that are used to evaluate student achievement are built on standard-referenced system. These types of tests focus on comparing the student's  performance with his peers'performance. The limitary of this type of evaluation in diagnosing thestudents'  acquisition  of  the  study  content  is  clarified,  because it focuses on what the student achieves on the light of his peers' standards and not the mastery standard that it is required to be achieved.  Also,  it  neglects the  diagnosis  and  remediation  of  thelearning weaknesses of that content. In order to remediate the weaknesses in this system the criterion-referenced measurement were suggested. It focuses on the diagnosis and measurement of what the students have accomplished, on knowledge and skills, on the light of specified criteria for performance that are agreed on previously.There are many specialists' attempts on designing and constructing criterionÂ referenced tests in different subjects such as mathematics to improve the learning-teaching process, and to classify students to masterly and non masterly students, and then remediate the weak points of the non masterly students. However, the researcher noted that there is a shortage of studies relevance to these tests on,Teaching mathematics in this country. Therefore, this studl aims to diagnose and evaluate the extent of learning mastery of the 3r  â€¢ Intermediate class students